The effect of graphene oxide on flame retardancy of polypropylene and polystyrene - Sabet, M. (ASTM International, 2020)
This study discusses how a graphene oxide (GO) has been developed to improve flame resistance, ignitability, and flame threats of polystyrene (PS) and polypropylene (PP). For reasons where high thermal stability alongside fire-resistant parts for vehicles or airships is essential, the manufacture of lightweight products appears to have promising outcomes. Cone calorimeter and limiting oxygen index experiments were used to measure heat and fire experiments of PS and PP nanocompounds. The incorporation of GO into PS and PP structures has reduced the heat release rate as measured through cone calorimeter. The characterization implied that without clear accumulations, the GO nanolayers were properly distributed throughout the PS structure, resulting in an outstanding upgrade of thermal strength and fire safety characteristics. During the ignition period, GO dispersal in PS and PP accelerated the ignition period and lowered the heat release rate. In addition, the incorporation of GOs reduced the PP's combustion rate as a result of developing a carbon protective layer that acts as a heat and mass transfer barrier. However, during combustion experiments, nanocompounds PS/GO and PP/GO generate a thermal insulation intumescent that protects the sublayers of the polymer. The peak of the heat release rate was reduced by 23 for PP/GO and 53 for PS/GO under flaming circumstances. The maximum thermal release rate indicates a substantial reduction for PP/GO 2.0 weight percent of nanocomposite compared to pure PP. This research shows that even GO inclusion does not change the limiting oxygen index values, but the development of an intumescent char protects the polymer sublayers properly. This feature offers a distinctive modification strategy to enhance GO's flame-resistant effectiveness. This research offers excellent insights into PP and PS nanocompounds' ignitability behavior with the inclusion of GO filler. This study delivers an appropriate choice to evaluate the potential for fire safety using graphene in polymers and flame-retarded polymers. Â© 2020 by ASTM International.